Synthesis of Controlled-Size Silica Nanoparticles from Sodium Metasilicate and the Effect of the Addition of PEG in the Size Distribution - Chapa-González, Christian (2018)
Silica nanoparticles are widely studied in emerging areas of nanomedicine because they are biocompatible, and their surface can be modified to provide functionalization. The size is intrinsically related to the performance of the silica nanoparticles; therefore, it is important to have control over the size. However, the silica nanoparticles obtained from sodium metasilicate are less studied than those obtained from tetraethyl orthosilicate. Moreover, the methods of surface modification involve several steps after the synthesis. In this work, the effect of different concentrations of sodium metasilicate on the size of silica nanoparticles was studied. In the same way, we studied the synthesis of organically modified silica nanoparticles in a one-step method, using poly(ethylene glycol). The nanoparticles were characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, and thermogravimetric analysis. It was found that the size distribution of the silica nanoparticles could be modified by changing the initial concentration of sodium metasilicate. The one-step surface-modification method caused a significant decrease in size distribution.